Um estudo sobre as formas de organização da formação pedagógica em cursos de licenciatura - Chaves, Taniamara Vizzotto (2014)
This research was developed within the Program of Postgraduate Studies in Education of the Federal University of Santa Maria (UFSM), in the research line “Formation, Knowledge and Professional Development” for the general thematic“formative processes of teachers” linked to the Group of Studies, Researches and Interventions INOVAEDUC. The focus of research is the pedagogical formation in Licentiate Degree Coursesand the main objective was to comprehend the ways of organizing of the pedagogical formation in Licentiate Degree Courses of the UFSM. We intend to contribute to discussions related to the organization of the curricula settings of Licentiate Degree Courses (LDC)on the perspective of articulation between the knowledge related to formation for the Disciplinary Area of Reference for the Teaching Matter (DARTM) and the Pedagogical Formation (PF). For that we seek to respond the following research problem: “What possibilities are presented for a pedagogical formation to the potential teachers on current curricula structuring of Licentiate Degree Courses of the UFSM?” Thus we developed a documental research involving seven LDC belonging to the Center of Naturaland Exact Sciences of the UFSM. The sources of information were the PPC, the Curricula Settings of the analyzed courses and the program of the discipline related to PF that are presented in curricula matrices of these courses.The research results indicate that the preparation and the teaching profession does not constitute as the main or sole focus of the LDC analyzed. As for distribution in the curricula matrices there was a preponderance of the disciplines related to DARTM regarding those related to PF, to the following aspects: work hours, amount of disciplines and disposition on the curricula matrices. By forms of organization evidenced, we understand that the initial formation in Licentiate Degree Courses analyzed is still strongly influenced by the model 3 + 1, with formation for teaching sometimes seen as an appendix of specific formation preventing the articulation between knowledge of the different conceptual fields. The Discipline of Specific Didactics is present in all curricula matrices and in some cases is the only related to the Matter Education. Except for the discipline of Methodology of the Research in Education, other disciplines related to Educational Sciences have the same codes, the same object of study but vary in terms of objectives, syllabuses and basic bibliography for different courses. The results permit to infer that the LDC analyzed lack of teacher identity which in our understanding may reflect on issues such as: abandonment, failure and evasion of the students of these courses and the sidelined of knowledge related to PF in relation to knowledge related to DARTM.